New Insight From the First Application of Ti-in-Quartz (TitaniQ) Thermometry Mapping in the Eastern Khondalite Belt, North China Craton - Zheng, Yuanyuan; Qi, Yang; Zhang, Di; Jiao, Shujuan; Huang, Guangyu; Guo, Jinghui (Frontiers in Earth Science, 2022)
The thermal regime of the lower crust is a critical factor that controls crustal anatexis, high-grade metamorphism, and granite formation, which finally results in crustal differentiation. However, the large-scale thermal regime in the Precambrian continental crust is generally not well established. In this study, we first applied Ti-in-quartz (TitaniQ) thermometer to map the temperature variation in the lower crust within an area of ~10000 km2 in the Paleoproterozoic eastern Khondalite Belt, North China Craton. The studied rocks are aluminous gneisses/granulites, which contain abundant quartz that generally coexists with rutile. The results show that matrix-type quartz with substantial rutile exsolution generally contains the maximum Ti concentration, which is <300 ppm higher than that of inclusion-type quartz. This result suggests that two quartz types probably formed at the prograde and near-peak to early cooling metamorphic stages, respectively. Therefore, the temperature mapping result based on the maximum Ti concentrations of the matrix-type quartz can better represent the thermal regime than inclusion-type quartz. Our regime shows that the hottest Paleoproterozoic lower crust is underneath the Liangcheng-Heling’er-Zhuozi area, where ultrahigh-temperature (UHT) metamorphism is closely associated with abundant charnockite. The hottest region may represent the root of an ancient large hot orogeny. Our study provides a new insight into the formation of UHT metamorphism.